1997
DOI: 10.1093/ps/76.10.1435
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin decreases pepsin output and gastrointestinal motility in chickens

Abstract: Two experiments were conducted to determine the effect of neurotensin on gastric secretion and gastrointestinal motility in conscious chickens. Chickens were surgically fitted with a cannula to collect secretions from the proventriculus and strain gauge transducers sutured to the gizzard, duodenum, and ileum in order to detect contractions. Peripheral intravenous infusion of physiological levels of neurotensin inhibited pepsin output from the proventriculus, but had no effect on the volume or pH of gastric sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The frequency of muscle contractions of the gizzard is depressed by pancreatic polypeptide in the chicken . Similarly, contractions of the gizzard are depressed in the presence of neurotensin (Degolier et al, 1997).…”
Section: Gizzardmentioning
confidence: 97%
See 1 more Smart Citation
“…The frequency of muscle contractions of the gizzard is depressed by pancreatic polypeptide in the chicken . Similarly, contractions of the gizzard are depressed in the presence of neurotensin (Degolier et al, 1997).…”
Section: Gizzardmentioning
confidence: 97%
“…Pepsin secretion from the proventiculus is depressed in the presence of neurotensin (Degolier et al, 1997). Histamine antagonists reduce release of acid (Guinotte et al, 1993).…”
Section: Proventriculusmentioning
confidence: 99%
“…In addition, the release of NT has been shown to be in response to lipid perfusion in the chicken duodenum [17]. These findings suggest that NT is involved in the post-prandial regulation of digestion, especially for lipid digestion [13]. In this study, realtime PCR analysis revealed the expression of NTR1 mRNA in chicken GI tract such as the proventriculus, gizzard, duodenum, jejunum, ileum, cecum, and colon/rectum, with remarkably abundant levels in the colon/rectum.…”
Section: Discussionmentioning
confidence: 88%
“…It has been demonstrated that NT inhibits pepsin output from the proventriculus as well as the frequency and strength of contraction and motility of chicken GI tract in vitro and in vivo [13,33]. In addition, the release of NT has been shown to be in response to lipid perfusion in the chicken duodenum [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hormones involved in gut regulation may be mediators for this; for example, (Gln4)-neurotensin, which is released in response to fat in the small intestine, seems to be involved in the regulation of lipid digestion 6,7 and may act as a hormone affecting the regional deposition of fat postprandially by regulating ATBF. 8 Gut hormones which could be involved include gastric inhibitory polypeptide, cholecystokinin, somatostatin and glucagon-like peptide.…”
Section: Introductionmentioning
confidence: 99%